Syntheses, Structures, and Properties of Two New Tri‐spin Lanthanide‐Nitronyl Nitroxide (LnIII = GdIII and HoIII) Complexes1. Issue 1 (26th September 2012) - Wang, Xiaoling; Xu, Panpan; Bao, Xia; Wang, Fengwu; Chen, Yonghong; Wei, Yijun
Abstract Abstract. Two radical–LnIII–radical complexes, [Ln(hfac)3(NITPh‐Ph)2] [Ln = Gd (1) and Ho (2), hfac = hexafluoroacetylacetonate; and NITPh‐Ph = 4′‐biphenyl‐4, 4, 5, 5‐tetramethylimidazoline‐1‐oxyl‐3‐oxide] were synthesized and characterized by X‐ray diffraction, elemental analysis, magnetic measurements, as well as IR and UV/Vis spectroscopy. X‐ray crystal structure analysis revealed that the structures of both complexes are isomorphous, the central LnIII ions are coordinated by six oxygen atoms from three hfac ligand molecules and two oxygen atoms from nitronyl radicals. The temperature dependencies of the magnetic susceptibilities were studied. They showed that in the GdIII complex, ferromagnetic interactions between GdIII and the radicals and antiferromagnetic interactions between the radicals coexist in this system (with JRad–Gd = 0.1 cm–1, JRad–Rad = –0.309 cm–1).